Evaluation of the awareness regarding Type 2 Diabetes, its management and adverse effects of the treatment among the patients with Type 2 Diabetes - Nizameddin Koca; Canan Ersoy; Banu Tatar (SERNEV, 2019)
Introduction: Diabetes Mellitus (DM) management requires not onlycontinuous medical care but also risk reduction strategies to preventcomplications. Improving patients' knowledge and awareness about DM anddiabetes-related complications (DRC) is crucial for the management of DM.Increased awareness about DM and DRC, which leads to an eagerness to follow-updiet plans, and lifestyle modifications would help us to establishpatient-specific goals. In this study, we would like to determine the awarenesslevels of diabetic patients about DM, DM management and DRC.Methods: Total of 300 adult patients (179 female, 121 male) with type 2 DiabetesMellitus (T2DM) were included in this study. The data was collected through asurvey based on face-to-face interviews. Total Survey score (TSP) for eachparticipant was calculated by taking 1 point for each correct answer and TSPinterval was evaluated between 0-24 points.. Results: The score of women was higher than that of men (14.72±3.14vs. 13.07±3.30, p lt;0.001). Patients who did not work were more aware(14.53±3.22 vs. 13.64±3.31, p = 0.019). No significant difference in terms ofawareness was observed between low educated and high-educated participants.Patients who had insulin in their treatment combination, anti-hypertensive, andlipid-lowering drug user had significantly higher TSP scores. A significantcorrelation was observed in BMI, HC, DBP, and age of Diabetes with awareness. Conclusions: The mean awareness score of the patients who participated in our study was14 points. Since the maximum score that can be obtained at the highestawareness level is 24, the awareness level of our patients can be evaluated as58%. Considering the morbidity, mortality and economic costs associated withdiabetes, it can be said that more attention should be paid to patienteducation in order to achieve higher treatment success.